Novel myo-inositol to butyrate fermentation pathway in the prevalent human gut species Dysosmobacter welbionis, a bacterium associated with improved metabolic and liver health. - Lee,C-H; Bui,TPN; Petitfils,C; Jian,C; Wong,GC; Puel,A; Le,Roy T; Bellais,S; Ben,Abdallah B; Nehlich,M; Leicht,T; Jia,M; et al. (Gut, 2026)
BACKGROUND: Dysosmobacter welbionis is a recently discovered butyrate producer whose presence in stool correlates with improved metabolic health. Whether its abundance is reduced in individuals with metabolic dysfunction-associated steatotic liver disease (MASLD) remains unknown. Mechanistic insight into its butyrate production from myo-inositol, a dietary compound from fruits, beans, grains and nuts with metabolic benefits, is also limited. OBJECTIVE: To assess population-level distribution, relative abundance and strain diversity of D. welbionis in humans, and to elucidate its metabolic capacity to ferment myo-inositol into butyrate. DESIGN: We analysed several human cohorts for associations with liver health and evaluated D. welbionis J115T supplementation in a diet-induced steatosis mouse model. An antibody-guided anaerobic cell-sorting strategy enabled isolation of distinct strains. We combined 13C-labelled inositol isotopes with NMR, mass spectrometry, genomics and proteomics. RESULTS: We found that D. welbionis and two related species (D. hominis and D. segnis) are prevalent gut bacteria in the human gut. D. welbionis abundance was reduced in MASLD across two cohorts and inversely correlated with fibrosis score in a third cohort. Treatment with D. welbionis J115T improved glycaemia and hepatic steatosis in high-fat diet fed mice. We identified a non-canonical myo-inositol-to-butyrate fermentation pathway. 19 human strains were isolated, comparative genomics of 23 strains revealed an open pangenome (about 2100 core genes) including the full myo-inositol fermentation pathway. CONCLUSION: D. welbionis possesses a unique, conserved route to convert dietary myo-inositol into butyrate, distinguishing it from other commensals and supporting its potential as a next-generation probiotic for metabolic and liver health.